SELF-RELIANT COMMUNIYT MANAGEMENT INNOVATION OF BAN KHIAM PHO, PAK CHALUI-DISTRICT, THA CHANG DISTRICT, SURAT THANI PROVINCE - Nakkul , Kwanrutai (Journal of MCU Nakhondhat, 2023)
The purpose of this article was to: 1) study the context of self-reliance community management of Ban Kiam Pho, and 2) study alternative strategies for creating innovation for self-reliance community management of Ban Kiam Pho, Pak Chalui Sub-district, Tha Chang District Suratthani province. The study was qualitative research by documentary data analysis with in-depth interview and focus group discussion. Data were selected by choosing a specific sample key informants such as 1) community leaders, 2) government agencies, 3) village health volunteers, 4) local philosophers, and 5) people total of 15 people for analyzed the information content and overview summarize. The research was found that: 1. Context of Ban Khiem Pho It was caused by the separation of the village from Village No. 4, Ban Na, Pak Chalui Sub-district, Tha Chang District, with a career in agriculture. and animal husbandry which has immigrated from all over the district and the Northeast buddhist and Christianity There is a tradition and culture that is Songkran, the tenth month festival and management of self-reliant communities, including technology, economics, natural resources, psychological, social and cultural aspects. And 2. study alternative strategies for creating innovation for self-reliance community management including: Proactive strategy (SO) which is to promote online trading training. Establishment of a community enterprise and promote the reduction of chemical, Corrective Strategies (WO) is to create cooperation from the government sector on careers and establish a product/distribution point in the community without passing through middlemen, Preventive Strategies (ST) is to promote the cultivation of a variety of crops harvested in all seasons. and herbs to treat disease, And Crisis strategy (WT) is to set up a health unit by using the knowledge of herbs for treatment. And ask for budget support from the public and private sectors.